Long-Term Outcomes after Acute Necrotizing Pancreatitis: What Happens to the Pancreas and to the Patient? - Winter Gasparoto, Rafaela Cristina Goebel; Racy, Marcelo de Castro Jorge; De Campos, Tercio (JOP. Journal of the Pancreas, 2015)
Context Late consequences of acute pancreatitis have received little attention. It is controversial whether the pancreas fully recovers after an episode of acute pancreatitis, especially in the presence of necrosis. Therefore, the presence of late pancreatic dysfunction following acute necrotizing pancreatitis is uncertain and there are controversies about how it may affect long-term quality of life. Objectives To evaluate pancreatic function and morphology, besides quality of life, in patients with prior acute necrotizing pancreatitis. Patients Patients who were admitted to our hospital with acute necrotizing pancreatitis in a ten-year interval were identified and thirty-eight survivors were contacted to enroll in the study out of which sixteen patients were included. Methods Exocrine function was studied by qualitative fecal fat excretion. Endocrine function was evaluated by oral glucose tolerance test, HOMA-beta and C-peptide. Pancreatic morphology was examined by computed tomography. Quality of life was measured by 36-item short-form health survey. Tests were performed at least twelve months after the index episode of acute necrotizing pancreatitis. Results The prevalence of pancreatic exocrine insufficiency was 6.2%. Endocrine dysfunction was observed in half the cases, and no association with the extension of necrosis was found. Morphological changes were frequent (62.5%) and more prevalent in those who faced extensive necrosis. Quality of life was considered good, and its impairment was found exclusively in mental health domain, markedly in patients who had alcoholic pancreatitis. There was no correlation between quality of life and prognostic indicators. Conclusions Exocrine function and quality of life were preserved in this group of patients. However, endocrine dysfunction and morphological abnormalities were frequent after acute necrotizing pancreatitis. These findings justify a long-term follow-up in order to initiate specific treatment promptly. Image: Santa Casa of São Paulo. São Paulo, Brazil